2012
DOI: 10.1021/jp306003e
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Ethene by Surface Methoxides: A Periodic PBE+D Study across Zeolites

Abstract: The role of zeolite topology in the stepwise methylation of ethene by surface methoxides was investigated. Density functional theory was employed in the determination of reaction mechanisms and energy barriers. Elementary steps were studied across multiple frameworks (i.e., BEA, CHA, FER, MFI, and MOR) constituting a wide variety of confinement environments. Surface methoxides were found to react with ethene through a transition state containing planar CH 3 species, which was best stabilized at the intersectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 106 publications
4
30
0
Order By: Relevance
“…A number of theoretical studies already addressed the importance of a stepwise mechanism. [73,[81][82][83]. In particular, it has been reported the stepwise mechanism becomes important at high temperature due to the entropic effect of the intermediate release of a water molecule [73,82].…”
Section: Adsorption Behaviour From Molecular Dynamics Simulationsmentioning
confidence: 99%
“…A number of theoretical studies already addressed the importance of a stepwise mechanism. [73,[81][82][83]. In particular, it has been reported the stepwise mechanism becomes important at high temperature due to the entropic effect of the intermediate release of a water molecule [73,82].…”
Section: Adsorption Behaviour From Molecular Dynamics Simulationsmentioning
confidence: 99%
“…In this stepwise mechanism, methanol first reacts with the catalyst framework, forming a methoxide species, which then transfers its methyl group to the HP species . Literature suggests that both mechanisms occur within the zeolite and the prevailing mechanism largely depends on the topology and the operating conditions . The studies show that with increasing temperature and decreasing pressure the prevailing mechanism shifts from concerted to stepwise .…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41][42][43][44] Literature suggests that both mechanisms occur within the zeolite and the prevailing mechanism largely depends on the topology and the operating conditions. [40][41][42][43][44][45][46][47][48][49] The studies show that with increasing temperature and decreasing pressure the prevailing mechanism shifts from concerted to stepwise. [45] This effect is attributed to the entropic gain of the intermediate release of water during the stepwise mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Then, they identified the number of van der Waals interactions and calculated the E LDE of the species of interest by applying the appropriate van der Waals coefficients. 7 De Moor and co-workers studied adsorption of alkanes in zeolites and showed that smaller pores lead to a tighter fit of adsorbates and thus to stronger adsorption, mainly due to higher contributions of the stabilizing van der Waals interactions between the n-alkane and the zeolite. 8 According to Sacchetto and co-workers, the knowledge of host−guest interactions occurring in zeolites could be helpful to improve adsorption properties of these materials, thus extending their application fields.…”
Section: Introductionmentioning
confidence: 99%